2001
DOI: 10.1002/1529-0131(200104)45:2<146::aid-anr167>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Open trial of methotrexate as treatment for autoimmune hearing loss

Abstract: Objective To assess the efficacy of low‐dose methotrexate (MTX) administered for the treatment of autoimmune hearing loss. Methods This was a prospective, 12‐month, open‐label study of 17 patients with refractory autoimmune hearing loss. All patients had ongoing episodic worsening of hearing in one or both ears prior to enrollment despite traditional medical therapy. The MTX dose was 7.5–25 mg/week. Hearing loss and vertigo were evaluated at baseline and at completion of the study. Hearing improvement was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Doses of 1 to 2 mg/kg/d of prednisolone have been used for 1 to 2 weeks and then tapered over a further 2 to 4 weeks depending upon disease severity and response. 3,4,[9][10][11] Those patients who are already deaf when treatment is started are much less likely to have improvement in their hearing. If steroids are not effective or if symptoms recur when they are tapered, other immunosuppressive drugs can be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses of 1 to 2 mg/kg/d of prednisolone have been used for 1 to 2 weeks and then tapered over a further 2 to 4 weeks depending upon disease severity and response. 3,4,[9][10][11] Those patients who are already deaf when treatment is started are much less likely to have improvement in their hearing. If steroids are not effective or if symptoms recur when they are tapered, other immunosuppressive drugs can be used.…”
Section: Discussionmentioning
confidence: 99%
“…If steroids are not effective or if symptoms recur when they are tapered, other immunosuppressive drugs can be used. 3,4,10,11 Previous case reviews have stated that patients with Cogan's syndrome receiving corticosteroids within the first 2 weeks of their hearing loss are those most likely to have an increase in their hearing acuity. Our patient had a rapid improvement in his hearing once commencing corticosteroids, despite it being 6 weeks from his initial symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have prospectively evaluated the treatment effects of methotrexate, including a total of 203 subjects (7,13,(24)(25)(26)(27). One double-blind, placebo-controlled, randomized controlled trial included 67 subjects with clinical AIED who had improved with a 1-month steroid treatment (13).…”
Section: Methotrexatementioning
confidence: 99%
“…Two other small prospective trials included 11 and 17 subjects (24,26). These studies included subjects with Ménière's disease and Cogan's syndrome, as well as primary AIED who had initial improvement with a trial of steroids, but subsequent deterioration.…”
Section: Methotrexatementioning
confidence: 99%
“…There have been several open-label and retrospective studies suggesting benefit of methotrexate (MTX) as a maintenance therapy in patients with AIED and Mé niè re disease who had responded to high-dose steroids. [31][32][33][34] Matteson and colleagues 32 found that 11 of 17 (65%) patients treated with MTX had benefit. However, efficacy of MTX is debatable.…”
Section: Managementmentioning
confidence: 99%